Reward-based Crowdfunding - Criteria of staggering success - Takáčová, Gabriela; Svobodová, Ivana, 1969-; Zaťko, Ivan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
This thesis provides recommendations on criteria leading to reward-based crowdfunding campaign success and their application to campaign preparation and execution. To navigate through the complexity of reward-based crowdfunding and to establish basis for the practical research the theoretical part reviews the most relevant topics of crowdfunding as well as the findings in the areas of campaign management, donor’s psychology and motivation. The practical part consists of the primary data collection through semi-structured qualitative interviews with stakeholders from founders and donors side. The application of selective coding method on the primary research reveals several significant criteria influencing crowdfunding campaign success, such as, investment of time and effort in pre-campaign; authenticity; addressing the right community, media and influencers; engaging campaign site and leveraging ones’ social network. These results are summarized in a practical step-by-step guide that can be used by founders to improve their chances of a successful reward-based campaign.
Vedoucí práce: Ivana Svobodová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses